التظاهرات السريرية خارج معوية عند مرضى التهاب الكولون القرحي - اسكيف نضال; انطانيوس ميلاد; شهوان شهوان (Latakia University Journal -Medical Sciences Series, 2019)
التهاب الكولون القرحي (UC) هو مرض التهابي مزمن مجهول السبب ومقتصر على الكولون. يتظاهر سريرياً بكثرة حدوث النزف المستقيمي، الزحير، المعص البطني. تهدف هذه الدراسة إلى الكشف الباكر عن اختلاطات التهاب الكولون القرحي. تضمنت الدراسة 50 مريضاً مصاباً بالتهاب الكولون القرحي (27 ذكراً و 23 أنثى)، تراوحت أعمارهم بالنسبة للذكور من 15-75 سنة، للإناث من 20-60 سنة، خلال مراجعتهم لمشفى الأسد الجامعي باللاذقية في الفترة الممتدة بين 1/8/2008 ولغاية 15/5/2009. تم تصنيف المرضى تبعاً لوجود تظاهرات خارج معوية أو غيابها. كانت التظاهرات خارج معوية الأكثر شيوعاً التي تم تحليلها هي: (مفصلية – جلدية – عينية). وجدت هذه التظاهرات عند 11 مريضاً (22%) (7 ذكور و 4 إناث، تراوحت أعمارهم بين 25-75 سنة).كان التهاب المفاصل المحيطي التظاهر الأكثر شيوعاً، حيث وجد عند 7 مرضى (63.3%). تم تشخيص التهاب الفقار اللاصق في حالة واحدة 9%. أظهرت دراستنا أن التهاب المفصل الحرقفي العجزي تظاهر مترافقاً مع تظاهرات خارج معوية أخرى إذ تم تشخيص حالتين 18%. تم تشخيص حمامى عقدة عند مريضين 18%. كما تم تشخيص التهاب القزحية في 3 مرضى (27.2%). يكون المرض أشد وأكثر امتداداً عند المرضى المصابين بالتهاب الكولون القرحي مع تظاهرات خارج معوية. Ulcerative colitis (UC) is an idiopathic chronic inflammatory disorder limited to the colon; the clinical manifestations of UC are rectal bleeding, tenesmus, and abdominal cramps. The aim of this study is to early detect the complications of UC. This study includes 50 patients, 27 males and 23 females, with ulcerative colitis. During their admission to Al Assad University Hospital in Lattakia between 1/8/2008 and 15/5/2009, their range of age is: male (15-75) years, female (20-60) years, The patients are grouped according to the presence or absence of extra intestinal manifestations. The most common extra intestinal manifestations (EM) (arthropathy, skin, ocular) has been analyzed. These manifestations are found in 11 (22%) patients (7 males and 4 females, aged 25-75 years). Peripheral arthritis is the most common EM; it is found in 7 (63.6%) patients. Kylosing spondilitis is diagnosed in one patient (9%). Our study shows that sarcolitis is detected in two patients 18%, accompanied by other EM. Erythrma nodosum is diagnosed in two patients (18%). Iritis is diagnosed in 3 patients (27.2%). On average, patients with EM have had more extensive and more active UC than others.